Analisis Keterampilan Abad ke-21 di STT Makedonia - Uliani Uliani; Meisakh Nur Anugrah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
21st century skills are very important to keep pace with the fast progress of science and technology. These skills must be mastered by students who will enter and interact directly with the community. The target of this community service is to see and assess the 21st century skills of Macedonian Theological College students which will be used as material for socialization to students. The total sample in this community service amounted to 28 students by filling out the questions asked in the questionnaire. Filling out this questionnaire includes five factors that become indicators, namely knowledge and technology literacy skills, critical thinking and solving skills, entrepreneurship and innovation skills, social responsibility and leadership skills, and career awareness. Assessment of 21st century skills will make it easier for educators to assist students in guiding and directing students to continue to train themselves and improve mastery of 21st century skills. Then the results of this study can be used as an illustration of 21st century skills at the Macedonian Theological College. The results found in this community service illustrate that Macedonian Theological College students have 21st century skills in a good category (Mean = 76.77).